Seasonality in low latitudes during the Oxfordian (Late Jurassic) reconstructed via high-resolution stable isotope analysis of the oyster Actinostreon marshi (J. Sowerby, 1814) from the Kachchh Basin, western India - Alberti, Matthias; Fürsich, Franz; Pandey, Dhirendra Kumar (International Journal of Earth Sciences, 2013)
A high-resolution stable isotope (δ18O, δ13C) analysis of a specimen of the oyster Actinostreon marshi (J. Sowerby, 1814) from the Lower Oxfordian of the Kachchh Basin in western India was used to reconstruct average seasonal temperatures over a consecutive time interval of 10 years. The recorded temperatures during this period varied around a mean of 13 °C (maximum: 15.1 °C; minimum: 11.4 °C) with a generally low seasonality between 1 and 3 °C. Such weak seasonal changes can be expected from a subtropical palaeolatitude between 25° and 30°S. However, the low average temperatures are in contrast to studies on broadly contemporaneous fossils from Europe and the southern Malagasy Gulf which point to much warmer conditions in these areas. It is therefore proposed that the low temperatures in the Kachchh Basin are caused by upwelling currents which influenced the north-western coast of India during the Late Jurassic. © 2013 Springer-Verlag Berlin Heidelberg.
UnivIS-Import:2017-12-18:Pub.2013.nat.dgeo.IGM.LP.season_3
Keywords: India; Jurassic; Kachchh Basin; Oxygen and carbon isotopes; Palaeoclimate; Palaeoseasonality